Current status of post-traumatic stress disorder among emergency nurses and the influencing factors - Qian, Yu-Fei; Liu, Ying; Wang, Li; Li, Qing; Sun, Rong-Qian (Frontiers in Psychiatry, 2023)
Objective: To gain a better understanding of the current state of traumatic stress experienced by emergency nurses of Grade III Level A hospitals in Jiangsu Province, as well as their coping styles after experiencing such traumatic events. Additionally, this study aims to identify the primary factors that influence the responses of these nurses to traumatic events. Methods: Using a cluster random sampling method, we enrolled 265 nurses working in the emergency departments of five Grade III Level A hospitals in Jiangsu Province. These nurses participated in a questionnaire survey that included inquiries regarding general information, previous traumatic experiences, and a post-traumatic stress disorder self-assessment scale (PCL-C) for emergency department nurses. Results: A total of 290 questionnaires were distributed, resulting in 265 valid questionnaires and an effective rate of 91.38%. These findings indicated that emergency nurses who participated in public health emergencies such as the COVID-19 pandemic (45.66%) and sudden health deterioration and death of patients (43.77%) encountered the most traumatic events. The top two traumatic events that had a moderate or greater impact on emergency nurses were verbal abuse from patients or their family members (39.24%) and verbal or physical threats by patients or their family members (35.09%). The mean PCL-C score of nurses who experienced traumatic events was 33.62 ± 11.37, with a positive rate of 26.04%. Results from the one-way analysis of variance and multiple linear regression analysis demonstrated that the working years, monthly income, and personal health status of emergency nurses were the main factors contributing to post-traumatic stress disorder.Conclusion: Emergency nurses are susceptible to severe traumatic stress following traumatic events, and effective interventions are necessary to address the diverse factors that contribute to their psychological well-being.